Cents and sensibility what economics can learn from the humanities - Morson, Gary Saul 1948; Schapiro, Morton Owen (Princeton University Press, 2017)
Economists often act as if their methods explain all human behavior. But in Cents and Sensibility, an eminent literary critic and a leading economist make the case that the humanities, especially the study of literature, offer economists ways to make their models more realistic, their predictions more accurate, and their policies more effective and just. Gary Saul Morson and Morton Schapiro trace the connection between Adam Smith's great classic, The Wealth of Nations, and his less celebrated book on The Theory of Moral Sentiments, and contend that a few decades later Jane Austen invented her groundbreaking method of novelistic narration in order to give life to the empathy that Smith believed essential to humanity. Morson and Schapiro argue that Smith's heirs include Austen, Anton Chekhov, and Leo Tolstoy as well as John Maynard Keynes and Milton Friedman. Economists need a richer appreciation of behavior, ethics, culture, and narrative--all of which the great writers teach better than anyone. Cents and Sensibility demonstrates the benefits of a freewheeling dialogue between economics and the humanities by addressing a wide range of problems drawn from the economics of higher education, the economics of the family, and the development of poor nations. It offers new insights about everything from the manipulation of college rankings to why some countries grow faster than others. At the same time, the book shows how looking at real-world problems can revitalize the study of literature itself.